Desain dan Uji Coba Media Pembelajaran Interaktif Menggunakan Articulate Storyline 3 Pada Materi Larutan Elektrolit dan Non Elektrolit - Zona Octarya; Fanny Fadhillah (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2023)
This research was instigated by the lack of learning media supporting teachers in explaining learning materials so that students were difficult to understand learning materials.  This research aimed at designing interactive learning media on Electrolyte and Nonelectrolyte Solution lesson with Articulate Storyline 3, and finding out the appropriateness of interactive learning media based on validity and practicality tests.  It was Research and Development referring to 4D development model with the steps: (1) define, (2) design, (3) develop, (4) disseminate.  Field testing was conducted to the tenth-grade students of Natural Science at Senior High School of Plus Bina Bangsa Pekanbaru.  The validation result scores by media and material experts were 94% and 96% with very valid criteria.  The score of practicality test by teacher was 96% with very practical criteria, and the score of student response test was 95.80% with very practical criteria.  Based on these findings, it could be concluded that interactive learning media on Electrolyte and Nonelectrolyte Solution lesson with Articulate Storyline 3 was appropriate to be used as learning media for students at school.